Ecovillage-Based Empowerment: A Collaborative Approach to Waste Management and Food Security in Air Anyir Village - Muhamad Khabib Cahyo Nugroho (Prospect Publishing, 2025)
The community empowerment program implemented in Air Anyir Village is a collaborative effort between PT PLN Nusantara Power Services Unit PLTU 3 Babel (PLTU Bangka), the local community, and the village government to address environmental and food security challenges. The main issues faced include suboptimal waste management and declining agricultural productivity due to land degradation. This program adopted a Participatory Rural Appraisal (PRA) approach and involved Focus Group Discussions (FGDs) with stakeholders across sectors. The program outcomes include the utilization of organic waste for duck feed and maggot cultivation, as well as the processing of FABA (Fly Ash and Bottom Ash) into organic fertilizer (PUFA) for agriculture. In addition, the program strengthens the local economy through the development of duck farming and coastal women-led MSMEs. The program has shown significant environmental impact by reducing waste by up to 600 kg per month and increasing participants’ income by 47%. Intergroup collaboration has also strengthened the village’s social networks, fostering an integrated empowerment ecosystem aligned with sustainable development goals.